Communication relative to transportation by railroads in the Confederacy : January 10, 1863 (Document (Virginia. General Assembly. Senate), 1863)
January 10, 1862 Communication of Governor Letcher to the Virginia General Assembly, transmitting Alabama resolutions regarding business and military transportation by railroads in the Confederacy.